General and Particular in the Formation and Development of Institute of Presidency in Post-soviet states - O. N. Grishaeva (Problemy Postsovetskogo Prostranstva, 2017)
In this article the author reveals the General and particular in development of Institute of presidency in post-socialist countries. The author compares the constitutional powers of the heads of States, noting the similarities and differences in their political development. After the collapse of the USSR in all republics adopted new constitutions and amendments thereto, reinforcing monofunctional system specifically created to resolve unusual acute economic, social and political problems. Today, the Institute of presidency in post-Soviet countries are diverse, and characterized its own characteristics, has specific features. The author’s notes that the post-Soviet space is not a monolith, and each political system can be a variety of achievements in a democratic transit. And if a number of some political systems choose the Western path of development, striving for the principle of the peaceful transfer of power and maximum democratizarea political discourse, others are very much dependent on the Soviet cultural inertia, a sense not involving the standards of democratization. There is another experience (Georgia, Ukraine, Kyrgyzstan), suggesting that the political system may be in a state of constant temptation. On the one hand, democratization and gradual reception of Western political standards, but on the other hand, the slow authoritarian drift. Some post-Soviet political system may experience the tendency to centralization, it is appropriate to their cultural code and historical traditions. On the contrary, in political systems that lean towards a different political tradition, could occur in reverse. Certainly, the experience of a particular post-Soviet political system and its choice in favor of one or another vector of development will assume a specific design of the presidency.